Global HR competencies : mastering competitive value from the outside in - Ulrich, David, 1953- (McGraw-Hill, 2013)
This book looks at best practices from companies on every continent, offering an expert survey of universal and regional HR dos and don'ts. Because new and developing global circumstances often require adaptability and changes in best practices, it documents the decision and policymaking of some of the world's foremost HR practitioners.